Eating disorder-related electrolyte abnormalities and adverse outcomes: A systematic review and meta-analysis - Deena Fremont; Amos Buh; Claire Hoar-Stephens; Nandini Biyani; Rohan Kiska; Stephen G. Fung; Shaafi Mahbub; Muhammad Zameer; Nicholas Fabiano; Marco Solmi; Maya Gibb; Rachel Kang; et al. (PLoS ONE, 2026)
Objective The aim of this study is to describe the association between electrolyte abnormalities and adverse clinical outcomes, as well as to estimate the prevalence of these abnormalities in individuals with eating disorders. Design Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2020-compliant systematic review searching Ovid MEDLINE, EMBASE, and PsycINFO databases from January 2000 to February 2025 was conducted. Methods We included studies with any electrolyte abnormality or clinical adverse outcome among individuals with eating disorders. We conducted two meta-analyses to assess (1) the odds of having an electrolyte abnormality among those with an eating disorder diagnosis compared to healthy controls, and (2) the prevalence of electrolyte abnormalities across eating disorder diagnoses. Results 20 studies incorporating 25,401 individuals were analysed, with most assessing a young female population. Study designs were predominantly retrospective cohort (n = 11) and cross-sectional (n = 5), with few including general population controls (n = 4). Anorexia nervosa was the most common eating disorder studied, with hypokalemia (n = 13 studies), hyponatremia (n = 11 studies), and hypophosphatemia (n = 7 studies) being the most frequently reported electrolyte abnormalities. The most prevalent adverse outcomes included anemia (n = 5 studies) and skeletal conditions (osteoporosis, osteopenia; n = 5 studies). The results from the meta-analyses showed (1) that individuals with eating disorders had significantly higher odds of experiencing electrolyte abnormalities compared to controls (OR = 3.20, 95% CI:1.48–6.94), and (2) varying pooled prevalences of abnormalities, including hypokalemia (15%), hyponatremia (13%), and hypophosphatemia (17%), across studies. Conclusion Electrolyte abnormalities are common among individuals with eating disorders and are associated with adverse health outcomes. Trial Registration The study was registered with the International Prospective Register of Systematic Reviews (PROSPERO) – (ID CRD42023477497)